2011
DOI: 10.1007/s00018-011-0660-3
|View full text |Cite
|
Sign up to set email alerts
|

Alternative pathways for MHC class I presentation: a new function for autophagy

Abstract: The classical view that endogenous antigens are processed by the proteasome and loaded on MHC class I molecules in the endoplasmic reticulum, while exogenous antigens taken up by endocytosis or phagocytosis are degraded and loaded on MHC class II in lysosome-derived organelles, has evolved along with the improvement of our understanding of the cell biology of antigen-presenting cells. In recent years, evidence for alternative presentation pathways has emerged. Exogenous antigens can be processed by the proteas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
1
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 76 publications
(146 reference statements)
2
49
1
5
Order By: Relevance
“…In order to be presented on MHC class I molecules, antigens must be processed to peptides, classically by the proteasome. However, it has recently been shown that antigens can be processed via the lysosome, following autophagy or mitophagy [9,10]. Matheoud et al now show that, in addition, mitochondrial proteins can be transported to the lysosome by MDVs for subsequent presentation on MHC class I molecules.…”
mentioning
confidence: 99%
“…In order to be presented on MHC class I molecules, antigens must be processed to peptides, classically by the proteasome. However, it has recently been shown that antigens can be processed via the lysosome, following autophagy or mitophagy [9,10]. Matheoud et al now show that, in addition, mitochondrial proteins can be transported to the lysosome by MDVs for subsequent presentation on MHC class I molecules.…”
mentioning
confidence: 99%
“…In contrast to the mostly cytoplasmic and ER production of the MHC class I peptidome, the class II peptidome is produced in a special compartment, associated with the endolysosome pathway (18 -20). This pathway is also thought to participate in the cross presentation of class I peptides, derived from proteins up-taken by professional antigen presenting cells (21), (reviewed in (15)(16)(17)22)). …”
mentioning
confidence: 99%
“…Interestingly, a recent study showed that, following autophagy, some viral Ags could be processed and directly loaded on MHC I within autophagolysosomal compartments (81). Thus, autophagy appears to be a possible route to take up cytosolic Ags and deliver them to endovacuolar compartments (23). However, our findings suggest a more complex Ag trafficking between endovacuolar compartments and the cytosol.…”
Section: Discussionmentioning
confidence: 56%
“…A variation of this latter pathway has been proposed in which Ags undergo cathepsin-dependent preprocessing in late endosomal compartments before they are transported to the cytosol where they are further processed by the proteasome (22). Thus, it seems that multiple pathways coexist and that they functionally cooperate with each other (23).…”
mentioning
confidence: 99%